Teori Keadilan John Rawls dan Tantangannya dalam Kebijakan Publik di Era Ketimpangan Sosial - Patingki, Fadliansa; Katili, Andi Yusuf; B, Virmansah (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2026)
Social inequality represents one of the major challenges faced by modern states in the formulation and implementation of public policies. Inequality is not limited to income distribution but also encompasses unequal access to education, healthcare, employment opportunities, and political participation. In this context, John Rawls’s theory of justice offers an important normative framework through the concept of justice as fairness, which emphasizes equal basic liberties and justifies social and economic inequalities only if they benefit the least advantaged members of society. This article aims to critically examine the relevance of Rawls’s theory of justice and the challenges of its application in public policy amid growing social inequality. The study employs a qualitative normative-theoretical approach based on an extensive literature review of Rawls’s works and contemporary scholarly discussions on social justice and public policy. The findings indicate that Rawls’s theory remains highly relevant as an ethical foundation for evaluating public policies, particularly in terms of distributive justice and fair equality of opportunity. However, the implementation of Rawlsian principles faces significant challenges, including the dominance of neoliberal policy paradigms, limited state resources, and the complexity of structural and global inequalities. This article concludes that Rawls’s theory cannot be applied mechanically but must be interpreted contextually to address contemporary socio-political dynamics. Nevertheless, Rawls’s theory continues to serve as a crucial normative compass for developing more just and inclusive public policies.